2014
DOI: 10.1016/j.scitotenv.2014.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant emissions during pyrolysis and combustion of waste printed circuit boards, before and after metal removal

Abstract: The constant increase in the production of electronic devices implies the need for an appropriate management of a growing number of waste electrical and electronic equipment.Thermal treatments represent an interesting alternative to recycle this kind of waste, but particular attention has to be paid to the potential emissions of toxic by-products. In this study, the emissions from thermal degradation of printed circuit boards (with and without metals) have been studied using a laboratory scale reactor, under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 44 publications
10
33
0
1
Order By: Relevance
“…In order of abundance, phenol, styrene and benzofuran were the most abundant products detected in all runs. This is in accordance with results obtained by Ortuño et al (2014a). In addition to these, some of the most important degradation products consisted in nonsubstituted polyaromatic compounds (i.e.…”
Section: (Figure 4)supporting
confidence: 92%
See 3 more Smart Citations
“…In order of abundance, phenol, styrene and benzofuran were the most abundant products detected in all runs. This is in accordance with results obtained by Ortuño et al (2014a). In addition to these, some of the most important degradation products consisted in nonsubstituted polyaromatic compounds (i.e.…”
Section: (Figure 4)supporting
confidence: 92%
“…Altarawneh and Dlugogorski (2014a) also found that the major product generated in the thermal decomposition of TBBPA was HBr. The total yield of HBr+Br 2 with the original PCB is similar as it is, only slightly higher than that detected in previous studies (Ortuño et al, 2014a). (Table 2) Figure 4 shows the results of emissions of the 16 priority PAHs during pyrolysis at 850ºC in the horizontal reactor.…”
Section: Hydrogen Halides and Halogenssupporting
confidence: 78%
See 2 more Smart Citations
“…(Conesa et al 2013). Similarly, the thermal processing of printed circuit boards, which represent around six percent of all e-waste by weight, is particularly problematic because of the heterogeneous combination of organic materials, metals and glass fiber (Ortuño et al 2014). Studies have demonstrated that emissions of PCDDs and PCDFs were lower than emissions of PBDDs and PBDFs, probably due to the higher bromine content of printed circuit boards.…”
Section: New Fuels -New Waste Streamsmentioning
confidence: 99%